Corrosion Behavior of Advanced High-Strength Steels (AHSS) in Chloride Solutions for Automotive Applications - Almeraya Calderón, Facundo; Montoya Rangel, Marvin; Jáquez Muñoz, Jesús Manuel; Lara Banda, María del Refugio; Estupiñan López, Francisco Humberto; Cabral Miramontes, José Ángel; Gaona Tiburcio, Citlalli (Molecular Diversity Preservation International, 2025)
The automotive industry utilizes high-strength low-alloy (HSLA) steels and advanced high-strength steels (AHSS) to manufacture various components, including front and rear rails, chassis, and roll bars, among others. In countries where de-icing salts are used, these steels are exposed to a localized corrosive environment. This research aims to characterize the corrosion behavior of AHSS [dual-phase (DP), ferrite–bainite (FB), and complex-phase (CP)] using electrochemical techniques such as cyclic potentiodynamic polarization (CPP) curves and electrochemical noise (EN), by immersing the steels in NaCl, CaCl2, and MgCl2 solutions. Optical microscopy (OM) is used to observe the microstructure of the tested samples. The CPP corrosion behavior of AHSS exposed to chloride solutions exhibits corrosion densities in the range of 10−2 and 10−3 mA/cm2. The results generally indicated that AHSS are susceptible to localized corrosion due to the presence of positive hysteresis in the CPP. Zn results show that DP780 presented higher corrosion resistance, with 845 Ω·cm2, whereas FB780 presented 253 Ω·cm2 when exposed to NaCl. Additionally, the type of corrosion is localized.